Community Service Through Science Practicum Guidance for SD IT Insantama Kendari, Southeast Sulawesi at the Integrated Laboratory Unit, Halu Oleo University - Sapto Raharjo; Lina Lestari Lestari; Muhamad Alim Marhadi; Yacobus Yulianto Dalanga; Sarman; Muhammad Arohman; Apriansa (Majalah Pengabdian Indonesia, 2026)
A magnet practicum mentoring activity for fifth-grade students of SD IT Insantama Kendari was conducted on 29 October 2025 at the Integrated Laboratory Unit of Halu Oleo University. The program was initiated to provide hands-on science learning in response to the school’s lack of laboratory facilities, which limits opportunities for practical experimentation. Eighteen students participated in three structured activities: identifying types of magnets, assembling a simple electric motor, and observing a flying ring demonstration. Learning was facilitated through demonstrations, guided discussions, and student-led experiments. The activity resulted in notable improvements in students’ conceptual understanding of magnetism, motivation to learn, and engagement during experimental tasks. The outcomes indicate that laboratory-based practicum activities significantly enhance meaningful science learning and contribute to strengthening scientific literacy among elementary students. Continued collaboration between schools and universities is recommended to ensure the sustainability of similar programs.